Peranan dan Cabaran Ekonomi Islam dalam Era Globalisasi: Suatu Analisis - Borhan, Joni Tamkin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2001)
Globalization has become the defining process of the present age. The most important aspects of economic globalization are the breaking down of national economic barriers, the international spread of trade, the financial and production activities, and the growing power of transnational corporations and international financial institutions in the process. While the opportunities and benefits of this process have been stressed by its proponents and supporters, recently there has been increasing disillusionment among many policy makers in the developing countries, analysts and academicians as well as community of non-governmental organizations (NGOs) in both Eastern and Western countries. The reasons for the changing perception of and attitude towards globalization are many. Among others are the lack of tangible benefits to most developing countries from opening their economy despite the well-publicized claims of export and income gains, the economic losses and social dislocation that are being caused to many developing countries by rapid financial, trade and investment liberalization, the growing inequalities of wealth and opportunities arising from globalization and the perception that environmental, social and cultural problems have been made worse by the working of the global free economy. In this connection, this article analyses the features of Islamic economy system, the nature of economy globalization, the failure of the conventional economy systems in the age of global village and the roles, and challenges of Muslim Ummah to globally impliment the Islamic economy system in the world countries.